Reproducibility of Glutamate, Glutathione, and GABA Measurements in vivo by Single-Voxel STEAM Magnetic Resonance Spectroscopy at 7-Tesla in Healthy Individuals - Gonen, Ofer M.; Moffat, Bradford A.; Kwan, Patrick; O’Brien, Terence J.; Desmond, Patricia M.; Lui, Elaine (Frontiers in Neuroscience, 2020)
Background and Purpose: Derangements in brain glutamate, glutathione, and γ-amino butyric acid (GABA) are implicated in a range of neurological disorders. Reliable methods to measure these compounds non-invasively in vivo are needed. We evaluated the reproducibility of their measurements in brain regions involved in the default mode network using quantitative MRS at 7-Tesla in healthy individuals. Methods: Ten right-handed healthy volunteers underwent 7-Tesla MRI scans on two separate days, not more than two weeks apart. On each day two scanning sessions took place, with a re-positioning break in between. High-resolution isotropic anatomical scans were acquired prior to each scan, followed by single-voxel 1H-MRS using the STEAM pulse sequence on an 8 mL midline cubic voxel, positioned over the posterior cingulate and precuneus regions. Concentrations were corrected for partial-volume effects. Results: Maximal Cramér-Rao lower bounds for glutamate, glutathione, and GABA were 2.0%, 8.0%, and 14.0%, respectively. Mean coefficients of variation within sessions were 5.9%±4.8%, 9.3%±7.6%, and 11.5%±8.8%, and between sessions were 4.6%±4.5%, 8.3%±5.7%, and 9.2%±8.7%, respectively. The mean(±SD) Dice’s coefficient for voxel overlap was 90%±4% within sessions and 86%±7% between sessions. Conclusion: Glutamate, glutathione and GABA can be reliably quantified using STEAM MRS at 7-Tesla from the posterior cingulate and precuneus cortices of healthy human subjects. STEAM MRS at 7-Tesla may be used to study the metabolic behavior of this important resting-state hub in various disease states.